Fink and Smith with dog sled team returing from hunt, Nome, Alaska, 1906 - Nowell, Frank H., 1864-1950
Handwritten on verso: F.W. Nowell photo, Nome, 1906. #4091. Fink and Smith returning from polar bear hunt in the Arctic, Distance traveled 100 miles. PH Coll 413.Album 9.29